Medias and Electronic Medias as one of the Factors affecting Pre-School Education - Atil lemoualdi, Awatef (Milev Journal of Research and Studies, 2021)
Pre-school education is a very important step in preparing children for primary school by developing their linguistic, kinetic, sensory, emotional and social skills. As long as education is a social system and dynamic process aims at shaping human behavior so that it conforms to dominant patterns of social organization, it is also subject to various influences arising from the social change phenomenon which is the most important technological factor, for its impact on the various systems and social patterns, including the cultural and educational factor. The electronic media and mass media are one of the information revolution products narrated by the human societies in the last quarter of the twentieth century, which brought about deep structural transformations in socialization methods and particularly in educational methods, where the media has become a competitor to traditional methods of education, including pre-school. Thus, the child is now living in the world of power of image, sound and speech, influenced by the programs which may affect their behavior and perception of the world, as well as their intellectual growth and sense of movement, which creates a discrepancy between what he acquires from media and what he receives in the pre-school, which is supposed to be preparatory for the subsequent school stage. From these points of view, we wanted to approach the subject from a sociological-educational perspective.